STRATEGI PENGELOLAAN SAMPAH PERMUKIMAN DENGAN POLA PENDEKATAN KARAKTERISTIK KAWASAN (STUDI KASUS KECAMATAN CAKRANEGARA KOTA MATARAM) - IDAA Warmadewanthi (Department of Environmental Engineering-Faculty of Civil, Environmental and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2005)
At present the human settlement in Cakranegara has faced solid waste problem. The service provided by the Mataram Municipal Cleansing Agency has not been satisfying. This study applied descriptive-explorative approach. Evaluation was performed towards traditional, culture, and Hinduism concepts of the community who lived in the center of Cakranegara. Results of this study showed that tradition, culture and Hinduism concepts, which were used as a base in solid waste management in the district center, was Tri Hita Karana. This term means prosperity and harmony. From the social culture point of view, solid waste reduction and reuse programs could be accepted in order to keep a harmonious relationship between man and the environment. Assuming that the targets of public participation of 2%/year in the sources of solid waste and 10% in the Transfer Depot, solid waste reduction may achieve 46,99% within 5 years through recycling and compost production.